The Adaptor Protein Myd88 Is a Key Signaling Molecule in the Pathogenesis of Irinotecan-Induced Intestinal Mucositis - Wong, Deysi V. T. (PLoS One, 2015)
Intestinal mucositis is a common side effect of irinotecan-based anticancer regimens. Mucositis causes cell damage, bacterial/endotoxin translocation and production of cytokines including IL–1 and IL–18. These molecules and toll-like receptors (TLRs) activate a common signaling pathway that involves the Myeloid Differentiation adaptor protein, MyD88, whose role in intestinal mucositis is unknown. Then, we evaluated the involvement of TLRs and MyD88 in the pathogenesis of irinotecan-induced intestinal mucositis. MyD88-, TLR2- or TLR9-knockout mice and C57BL/6 (WT) mice were given either saline or irinotecan (75 mg/kg, i.p. for 4 days). On day 7, animal survival, diarrhea and bacteremia were assessed, and following euthanasia, samples of the ileum were obtained for morphometric analysis, myeloperoxidase (MPO) assay and measurement of pro-inflammatory markers. Irinotecan reduced the animal survival (50%) and induced a pronounced diarrhea, increased bacteremia, neutrophil accumulation in the intestinal tissue, intestinal damage and more than twofold increased expression of MyD88 (200%), TLR9 (400%), TRAF6 (236%), IL–1β (405%), IL–18 (365%), COX–2 (2,777%) and NF-κB (245%) in the WT animals when compared with saline-injected group (P<0.05). Genetic deletion of MyD88, TLR2 or TLR9 effectively controlled the signs of intestinal injury when compared with irinotecan-administered WT controls (P<0.05). In contrast to the MyD88(-/-) and TLR2(-/-) mice, the irinotecan-injected TLR9(-/-) mice showed a reduced survival, a marked diarrhea and an enhanced expression of IL–18 versus irinotecan-injected WT controls. Additionally, the expression of MyD88 was reduced in the TLR2(-/-) or TLR9(-/-) mice. This study shows a critical role of the MyD88-mediated TLR2 and TLR9 signaling in the pathogenesis of irinotecan-induced intestinal mucositis.